2014
DOI: 10.2113/econgeo.109.7.1901
|View full text |Cite
|
Sign up to set email alerts
|

Trace Element Geochemistry of Magnetite and Its Relationship to Cu-Bi-Co-Au-Ag-U-W Mineralization in the Great Bear Magmatic Zone, NWT, Canada

Abstract: The Paleoproterozoic Great Bear magmatic zone is the focus of ongoing exploration for iron oxide coppergold (IOCG) deposits and also hosts iron oxide-apatite occurrences. Examples of IOCG deposits in the Great Bear magmatic zone include Sue-Dianne and NICO, and other smaller prospects, including Damp, Fab, and Nori/Ra. The past-producing Terra mine property hosts significant IOCG-like alteration that contains domeshaped, iron oxide-apatite bodies. Petrographic study has identified multiple generations of magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 63 publications
2
22
0
Order By: Relevance
“…Iron oxide copper-gold styles of mineralization and IOA ± actinolite mineralization are recognized throughout the Great Bear magmatic zone, where they are spatially and temporally related to one another and extensive magmatism (Badham and Morton, 1976;Hildebrand, 1986;Gandhi, 1994;Goad et al, 2000;Mumin et al, 2007Mumin et al, , 2010Corriveau et al, 2010a, b;Potter et al, 2013;Somarin and Mumin, 2014;Acosta-Góngora et al, 2014, 2015a accepted with revisions; Mumin, 2015). We present a large-scale overview of the Great Bear magmatic zone and its geodynamic setting.…”
Section: Accepted M Manuscriptmentioning
confidence: 94%
See 2 more Smart Citations
“…Iron oxide copper-gold styles of mineralization and IOA ± actinolite mineralization are recognized throughout the Great Bear magmatic zone, where they are spatially and temporally related to one another and extensive magmatism (Badham and Morton, 1976;Hildebrand, 1986;Gandhi, 1994;Goad et al, 2000;Mumin et al, 2007Mumin et al, , 2010Corriveau et al, 2010a, b;Potter et al, 2013;Somarin and Mumin, 2014;Acosta-Góngora et al, 2014, 2015a accepted with revisions; Mumin, 2015). We present a large-scale overview of the Great Bear magmatic zone and its geodynamic setting.…”
Section: Accepted M Manuscriptmentioning
confidence: 94%
“…Type examples occur in the Camsell River area, adjacent to the Terra polymetallic vein deposit ( Fig. 2A-B; Badham and Morton, 1976;Hildebrand, 1986) and in the Echo Bay area (Reardon, 1992;Somarin and Mumin, 2014); less-voluminous examples occur throughout the Great Bear magmatic zone as veins, breccia cements, and replacements (Table 1: Gandhi, 1994;Corriveau et al, 2007Corriveau et al, , 2010bMumin et al, 2007Mumin et al, , 2010Potter et al, 2013;Acosta-Góngora et al, 2014).…”
Section: Iocg and Ioa Depositsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the inclusions formed under equilibrium conditions, then the micrometer-scale domains sampled by EPMA and LA-ICP-MS should provide information about the fluid composition. In contrast, if inclusions formed under disequilibrium conditions, then large variations in trace element contents are expected to characterize the iron oxide composition measured by EPMA and LA-ICP-MS.Iron oxide trace element composition of IOCG(Carew 2004;Rusk et al 2009Rusk et al , 2010Dupuis and Beaudoin 2011;Zhang et al 2011;Acosta-Góngora et al 2014;Chen et al 2015; De Toni 2016) andIOA (Müller et al 2003; Knipping et al 2015a, b;Heidarian et al 2016;Velasco et al 2016;Broughm et al 2017) deposits have been reported. In most studies, the trace element composition of iron oxides is used to discuss the factors controlling compositional variations and the formation of mineralization.…”
mentioning
confidence: 99%
“…The composition of magnetite is particularly useful for evaluating ore-forming processes, as its composition is controlled by numerous factors, including: temperature, source rock/fluid composition, oxygen and sulfur fugacity, silicate and sulfide activity, host rock buffering, re-equilibration processes, and intrinsic crystallographic controls (i.e., ionic radius and charge balance) (e.g., Nadoll et al 2014). Magnetite-bearing ore deposits include Ni-Cu-PGE, BIF, iron oxide-Cu-Au (IOCG), skarn, porphyry Cu, Fe-REE-Nb, Cu-Au-Fe, iron oxide-apatite, and volcanogenic massive sulfide deposits (VMS) (e.g., Acosta-Góngora et al, 2014;Chen et al, 2014;Chung et al 2014;Dare et al, 2012;Dupuis and Beaudoin 2011;Huang et al, 2014;Makvandi et al, 2015;Nadoll et al, 2012;Pagé and Barnes, 2009;Pisiak et al 2015;Xu et al, 2014;Zhao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%